Metabolic syndrome in shift healthcare workers - d'Ettorre, Gabriele; Pellicani, Vincenza; Greco, Mariarita; Mazzotta, Mauro (La Medicina del Lavoro, 2019)
Background: Shift work including night shifts is generally associated with chronic misalignment between the endogenous circadian timing system and behavior cycles, leading to metabolic disorders including metabolic syndrome (MS). Objectives: The purpose of this research was to analyze the latest developments in assessing and managing the occupational risk of MS in shift-healthcare workers (HCWs). Methods: According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, the authors used MEDLINE/Pubmed to perform a systematic review of literature from January 2008 to December 2018.  Results: Six studies were selected; the topics, discussed in order of frequency from highest to lowest, were: risk assessment, occurrence rates, and risk management. The main occupational determinants for MS were the cumulative shift work including night shifts and the number of nights worked per month per worker. With regard to cumulative lifetime exposure to shift work, the findings of our review suggest a dose–response relationship between increasing years of shift work history and MS in shift-HCWs. Conclusions: The findings suggest the need to better investigate the impact of sleep deprivation in the assessment of MS risk in shift-HCWs and clarify the role of such variables as confounders, mediators, or effect modifiers. Moreover, to date the data regarding management interventions focused on the risk of MS are inconsistent and therefore a special effort is required to detect strategic ways to minimize the likelihood of MS occurring in shift-HCWs.